LEGAL REPRESENTASIONAL SEBAGAI UPAYA MENINGKATKAN NILAI ASET EKSTRALEGAL PELAKU USAHA EKONOMI KREATIF SEKTOR PARIWISATA - Jusmadi, Rhido; Sumriyah (JUSTITIA JURNAL HUKUM, 2023)
The presence of creative economy entrepreneurs in the tourism sector as one of the people's economic units has made a significant contribution to the economic development process in Indonesia, particularly in poverty eradication efforts. The simple assets traditionally owned by creative economy entrepreneurs in the tourism sector surprisingly hold considerable economic value potential. However, this significant potential is often overlooked due to its status as an extralegal asset, not recognized within the existing legal protection system. Consequently, the existing system does not acknowledge the legitimacy of these assets, rendering them lacking a strategic economic basis since they cannot be used as collateral to secure capital. Given this scenario, there is a need for an approach in the form of a legal representational model, serving as an alternative policy or regulation to transform the potential of extralegal assets owned by creative economy entrepreneurs in the tourism sector into productive capital. This transformation aims to add value to production capacity (capitalization of assets) and ensure protection within the prevailing formal legal system. The legal representational model can serve as a solution to enhance the potential of resources held by creative economy entrepreneurs in the tourism sector, contributing to the economic capacity of the region to achieve the well-being and prosperity of the local communities.